Os processos de ovulação e reinício da meiose oocitária são mediados pela interação entre angiotensina ii, progesterona e prostaglandinas - Siqueira, Lucas Carvalho (2011)
Angiotensin II (AngII), progesterone (P4) and prostaglandins (PGs) are essential for ovulation of a fertile oocyte. This study sought to understand how these factors are linked together during the ovulatory process. To this end, first we characterized the pattern of expression of genes of interest to the renin-angiotensin system in follicular cells and AngII concentration in the fluid during the periovulatory period. Cows were ovariectomized at various times after GnRH injection to obtain pre (at the time of GnRH treatment) and periovulatory follicles (3, 6, 12, and 24 h after GnRH treatment). Theca and granulosa cells were separated and processed to real time RT-PCR Herein we demonstrated that the gonadotropin surge stimulates the follicular secretion of AngII and theca cells expression of mRNA for AGTR2 receptors. Next, we assessed whether AngII can modulate the secretion of steroids and PGs by follicular cells using in vitro culture of theca and granulosa cells of bovine ovaries from abattoir. In this study we found that AngII in synergism with LH stimulates the synthesis of PGE2 and PGF2α and P4 by granulosa cells. The role of AngII and PGs as mediators of nuclear maturation of oocytes in ruminants induced by gonadotropins had already been demonstrated. However, a similar action performed by P4 is still controversial in cattle. In this work, using in vitro and in vivo models, we evidenced that P4 not only participates in this process, but it is also an intermediate factor between AngII and PGs in the cascade of events. With the present work is possible to conclude that AngII, P4 and PGs are "linked" mediators of the preovulatory gonadotropin surge. These data allowed us to propose a unified model for both, ovulation and the resumption of nuclear maturation of oocytes. In this model the preovulatory gonadotropin surge up regulates the production of AngII and follicular expression of AGTR2 receptors, stimulating the secretion of P4 and the release of PGE2 and PGF2α, culminating with the ovulation of a fertile gamete.